Effects of Physical and Mental Fatigue on Postural Sway and Cortical Activity in Healthy Young Adults - Gebel, Arnd; Busch, Aglaja; Stelzel, Christine; Hortobágyi, Tibor; Granacher, Urs (Frontiers in Human Neuroscience, 2022)
Physical fatigue (PF) negatively affects postural control, resulting in impaired balance performance in young and older adults. Similar effects on postural control can be observed for mental fatigue (MF) mainly in older adults. Controversial results exist for young adults. There is a void in the literature on the effects of fatigue on balance and cortical activity. Therefore, this study aimed to examine the acute effects of PF and MF on postural sway and cortical activity. Fifteen healthy young adults aged 28±3 years participated in this study. MF and PF protocols comprising of an all-out repeated sit-to-stand task and a computer-based attention network test, respectively, were applied in random order. Pre-post fatigue, cortical activity and postural sway (i.e.,centre of pressure displacements [CoPd], velocity [CoPv], and CoP variablity [CVCoPd,CVCoPv]) were tested during a challenging bipedal balance board task. Spectral power was calculated for theta (4-7.5Hz), alpha-2 (10.5-12.5Hz), beta-1 (13-18Hz), and beta-2 (18.5-25Hz) in frontal, central, and parietal regions of interest (ROI) and baseline-normalized. Inference statistics revealed a significant time-by-fatigue interaction for CoPd (p=.009,d=0.39,Δ9.2%) and CoPv (p=.009,d=0.36,Δ9.2%), and a significant main effect of time for CoP variability (CVCoPd:p=.001,d=0.84;CVCoPv:p=.05,d=0.62). Post-hoc analyses showed a significant increase in CoPd (p=.002,d=1.03) and CoPv (p= 003, d=1.03) following PF but not MF. For cortical activity, a significant time-by-fatigue interaction was found for relative alpha-2 power in parietal (p<.001,d=0.06) areas. Post-hoc tests indicated larger alpha-2 power increases after PF (p<.001,d=1.69,Δ3.9%) compared to MF (p=.001,d=1.03,Δ2.5%). Additionally, changes in parietal alpha-2 power and measures of postural sway did not correlate significantly, irrespective of the fatigue protocol. No significant changes were found for the other frequency bands, regardless of the fatigue protocol and ROI under investigation. Thus, the applied PF protocol resulted in increased postural sway (CoPd and CoPv) and CoP variability accompanied by enhanced alpha-2 power in the parietal ROI while MF led to increased CoP variability and alpha-2 power in our sample of young adults. Potential underlying cortical mechanisms responsible for the greater increase in parietal alpha-2 power after PF were discussed but could not be clearly identified as cause. Therefore, further future research is needed to decipher alternative interpretations.